ANALISIS KINERJA KEUANGAN PADA KOPERASI WREDATAMA HARUM KABUPATEN BREBES - Sri Ratih Handayani (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2016)
ABSTRACT This study aims to determine the analysis of financial performance at the Wredatama Harum Cooperative. The subjects in this study were the financial performance of the Wredatama Harum Cooperative in Brebes Regency in terms of liquidity, solvency, and profitability. The data sources used were secondary data obtained from data or records from the examiner's report on the Wredatama Harum Cooperative in Brebes Regency. The results of the study show that assets are sufficiently liquid in paying short-term obligations. With a good level of solvency and the level of profitability, it is concluded that the ability of cooperatives to generate profits is good. Keywords : liquidity ratio, solvency ratio,profitability ratio